DIGITALIZATION MODEL OF MARKETING, FINANCE AND CONTRACTS IN MSMES PERTAKINA BLITAR - Fedianty Augustinah; Dian Ferriswara; Sri Astutik; Vieta Imelda Cornelis (International Conference on Business Management and Accounting, 2022)
Optimization of MSMEs, one of the goals is to accelerate the recovery of the national economy, which is dominated by Micro and Medium Enterprises (MSMEs). The formulation of the problems in this study is 1) how the marketing digitalization model for MSMEs in Pertakina Blitar as a means of promotion so far, 2) how the financial digitization model for MSMEs in Pertakina Blitar as a tool to make it easier to make financial reports, 3) how is the digitalization model of employment contracts for MSMEs in Pertakina Blitar. Thebenefits of this research are 1) the results of this study are expected to provide the latest information or the latest updates on marketing / marketing digitalization, digitalization of finance and digital work contracts on MSMEs in Pertakina Blitar. The findings and recommendations of this study are expected to be input for policy makers and policy implementers to improve the digitalization management model for MSMEs Pertakina Blitar, 2) the draft digital marketing management model, financial digitization and digital work contracts are expected to be a model system in the following research with applications that can be applied more simply and can be applied to MSMEs Pertakina Blitar. This means that this system can be operated at MSMEs in Pertakina Blitar, whereby using digitalization, MSME products in Pertakina Blitar can be more affordable anytime and anywhere by consumers. Qualitative research methods are research methods based on the philosophy of postpositivism used to examine objects with natural conditions (real state, not set or in an experimental state) in which the researcher is the key instrument. The research subjects were determined based on the focus of the study, including: (1) 14 MSMEs who are members of Pertakina, (2) MSMEs that are directly or indirectly involved in the management of marketing, finances, and contracts where they are increasingly representative. Collecting data and information generated through observation methods, in-depth interviews, FGDs, and analysis of texts, documents, and digital files. The information obtained during in-depth interviews with several MSMEs who members of the Pertakina Blitar community are shows that the model of digitalization of marketing in MSMEs is not carried out optimally, and some have not even promoted through electronic marketing, nor have they recorded regularly in financial administration and have never done a written work contract, let alone electronically. MSMEs who are members of the Pertakina Blitar community need an increase in skills and abilities in their human resources through training and assistance in digital marketing, training on financial recording and digital finance as well as assistance at the same time, training on making written contracts and digital contracts. Downstreaming of the digital economy of MSMEs and Cooperatives in Indonesia, the problem is that digital literacy is still low, production capacity is inadequate, production quality is inconsistent or relatively low.